16‐2: A 4‐inch Full Color Active‐matrix Mini‐LED Display based on 0408 Chip and 500um Pixel. Issue 1 (25th September 2020) - Yin, Yongming; Sun, Yang; Gao, Lu; Fan, Jack; Zhang, Lijun; Liu, Minggang; Hua, Zhiheng; Yang, Bo; Wang, Zeng; Fu, Jianhang; Liang, Pengfei; Hwang, Jason; et al.
Abstract : Mini/Micro LED are recognized as the fourth generation display technology due their superior performance. Backlights based on active‐matrix Mini‐LED (AM‐MLED) have been adopted in LCD modules and would soon be put into mass production. In this paper, a 4‐inch full‐color AM‐MLED Display based on 0408 chip and 500um pixel pitch was presented. The chip size and pixel pitch reported here are smallest till now for AM‐MLED based on glass backplanes. We believe this result would further extend the application of Mini‐LED in direct display area.